Foreign source for teaching Russian to students on the basis of an animated approach - N. M. Nematova (Genius Journals, 2022)
This article provides information about foreign sources in teaching Russian based on the concept of animation and an animated approach to t alabas
Keywords: Russian; animation; ACT; methodology